Too little and too much: investigating the role of balanced prefrontal neural activity in behavioural flexibility - Hock, Rebecca M. (2020)
A consistent deficit of schizophrenia, among numerous neuropsychiatric disorders, is impaired cognitive flexibility, the prefrontal-dependent ability to overcome pre-existing behavioural strategies to adjust behaviour in line with changing environmental demands. Prefrontal gamma-aminobutyric acid (GABA) dysfunction has been linked to these cognitive impairments and there is evidence that tasks requiring cognitive flexibility require the medial prefrontal cortex (mPFC) and local GABA-mediated transmission. In this thesis, I report five experiments in which an operant strategy shifting task was used to test whether both increased and decreased GABA inhibition in the mPFC impair strategy shifting in Lister Hooded rats. In experiment 1, prefrontal hypo-activation or functional disinhibition was induced by micro-infusing the GABAA agonist muscimol (62.5ng/side) or antagonist picrotoxin (PTX) (300ng/side) respectively, into the mPFC; these manipulations had markedly impaired sustained attention in a 5-choice serial reaction time (5CSRT) test during previous research. Results showed that neither prefrontal hypo-activation nor disinhibition affected shifting from a spatial response to a visual light-cue-based response, although disinhibition impaired expression of the spatial response and increased trial omissions. Remarkably, all rats required up to three times the number of trials to shift the responses as compared to previous studies in other rat strains. Two additional behavioural studies without infusions followed; experiment 2 showed removal of pre-training cue-light pre-exposure and reduction of training trials for the initial spatial response strategy did not facilitate shifting to cue-based strategy; experiment 3 showed rats could acquire the cue strategy and then shift to the spatial response strategy, and also perform spatial response reversals, within a similar number of trials as in previous studies. Ultimately, however, there was always a substantially higher shift cost for response-to-cue than for the cue-to-response shift (~ 200 trials). Experiment 4 investigated effects of mPFC disinhibition and hypo-activation on shifting from cue to response strategies, and there is evidence to suggest prefrontal picrotoxin disrupted shifting ability, impaired expression of rule retrieval following rule acquisition, and response latency. Additionally, experiment 5 found that administering the same prefrontal disinhibition, prior to initial rule acquisition, as well as prior to strategy shifting, increased perseveration. Finally, a Bayesian analysis approach was used to infer the types of learning strategies that rats were using during task performance, with preliminary results suggesting that rats predominantly use a lose-shift strategy during the first trials of shifting to a spatial response. From these data one conclusion is that when present during initial rule learning prefrontal disinhibition may augment reward-association, and impair expression of newly learnt shift rules, thus increasing perseveration.